EFEKTIVITAS PENERAPAN MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Puspayanti, Sri; Anak Agung Gede Agung; Chindytia; Ni Kadek Sri Puspayan; I Made Lolyn Agastyapranayoga; Putu Ratih Wibaniti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of School Based Management (SBM) implementation in improving the quality of education at SD Negeri 6 Panjer. This study used a qualitative descriptive approach with a case study method. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The questionnaire instrument consisted of curriculum management, student management, human resource management, financial management, infrastructure management, public relations management, and excellent service management. The results showed that the implementation of SBM at SD Negeri 6 Panjer has been implemented quite effectively through the principles of participation, transparency, accountability, and school independence. Supporting factors include competent teachers, a conducive school environment, and democratic leadership of the principal. Meanwhile, inhibiting factors include limited facilities and infrastructure, limited funding, and uneven stakeholder participation. Therefore, continuous collaboration between schools, parents, and stakeholders is needed to improve the quality of education through effective SBM implementation.